Behavioral flexibility facilitates the use of spatial and temporal refugia during variable winter weather. (10th January 2022) - Gilbert, Neil A; Stenglein, Jennifer L; Van Deelen, Timothy R; Townsend, Philip A; Zuckerberg, Benjamin
Abstract: In North America, winters are becoming more variable such that warm and cold extremes are increasingly common. Refugia (in time or space) can reduce the exposure animals experience to extreme temperatures. However, animals must be able to adjust their behavior to capitalize on refugia. Our goal was to identify the behavioral mechanisms that grant access to refugia in time and space, focusing on a northern ungulate (white-tailed deer, Odocoileus virginianus ) as a model. We drew upon an extensive camera trap network in Wisconsin, USA, over two winters that experienced both warm and cold extremes. To understand the use of temporal refugia, we modeled deer activity (at daily resolution) during night, dawn, day, and dusk as a function of weather predictors. To understand the use of spatial refugia, we modeled deer activity at camera locations (at daily resolution) as a function of landscape characteristics, weather conditions, and landscape–weather interactions. During anomalously cold temperatures, deer became more diurnal; conversely, on anomalously warm days, deer were more nocturnal. Deer were more active in conifer-dominated landscapes on cold days. Conversely, during warm extremes, deer increased activity in deciduous-dominated landscapes. Finally, deer showed multiple modes of behavioral flexibility (activity in time as well as space) and demonstrated stronger responses to temperature anomalies later in the winter, suggesting that the effects of extreme events are dependent upon their seasonal timing. Behavioral shifts presumably reduce exposure to extremes and may render species more resilient to increasingly variable winter climates. Abstract : On-the-fly adjustments to behavior are the first line of defense against short-term climatic extremes. During winter cold waves, deer changed their behavior in time (becoming more active during daylight hours) and space (showing greater activity in conifer-dominated landscapes), adjustments that presumably reduce their exposure to extremely cold temperatures. Conversely, during winter warm waves, deer were more night-active and more likely to use deciduous-dominated landscapes, which provide less buffering against cold temperatures.